Critical distance model for the fatigue life analysis under low-velocity impacts of notched specimens. (May 2021) - Gao, Daiyang; Yao, Weixing; Wen, Weidong; Huang, Jie
Highlights: Strain history of variable amplitudes is caused by constant repeated impacts. Mean stress compensation on the Manson-Coffin equation by Morrow's method. Stress gradient effect considered by the Theory of Critical Distance. Impact fatigue experiment on the plate specimens of two types of notches. Critical distance method for impact fatigue life estimation on notched structures. Abstract: A fatigue life estimation method is proposed for the notched specimens under low-velocity repeated impact loadings. The stress concentration effect at the notch root is taken into account by the implementation of the Theory of Critical Distance, and the continuous variation of strain ranges at the critical point due to the plastic strain accumulation is considered by the mean strain modification. The impact fatigue experiment is conducted on the notched plate specimen of material S45C with the pendulum-type test machine, and the comparison with the numerical analysis results indicates that the proposed model gives a satisfactory prediction on the impact fatigue lives.